2020
DOI: 10.1002/mde.3114
|View full text |Cite
|
Sign up to set email alerts
|

Are China's subsidies for electric vehicles effective?

Abstract: China has implemented high subsidy schemes to promote the adoption of electric vehicles. This study constructs an industrial organization model to theoretically analyze and numerically simulate the subsidy efficacy of battery electric vehicles in China. We find that subsidies for battery manufacturers and those for electric vehicle manufacturers are equivalent. Fixed subsidies are better for social welfare maximization than linear subsidies are. Simulation based on Chinese empirical data shows that China's sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…Harvey et al found that the government should cut or stop electric vehicle subsidies for environmental benefits (Harvey, 2020). Deng and Tian found that avoiding excessive subsidies can prevent NEV manufacturers from defrauding the government to obtain grants (Deng and Tian, 2020). Santos and Rembalski and Ye et al reached the opposite conclusions from the perspective of sustainable development: The former mainly considered the current high NEV production costs and emphasized the need for subsidies in the short term; the latter mainly considered market demands and technological development, and proposed that replacing product subsidies with alternative policies, such as the unlimited driving policy, can promote the endogenous development of the NEV industry (Santos and Rembalski, 2021;Ye et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Harvey et al found that the government should cut or stop electric vehicle subsidies for environmental benefits (Harvey, 2020). Deng and Tian found that avoiding excessive subsidies can prevent NEV manufacturers from defrauding the government to obtain grants (Deng and Tian, 2020). Santos and Rembalski and Ye et al reached the opposite conclusions from the perspective of sustainable development: The former mainly considered the current high NEV production costs and emphasized the need for subsidies in the short term; the latter mainly considered market demands and technological development, and proposed that replacing product subsidies with alternative policies, such as the unlimited driving policy, can promote the endogenous development of the NEV industry (Santos and Rembalski, 2021;Ye et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…With simulations that were based on different propositions, an analysis was conducted. Although subsidies give benefits, the study revealed that in order for them to be optimal, some rules and holistic calculations regarding the structure and gaining of these government subsidies are required (Deng & Tian, 2020). Some of the studies in the literature have chosen to apply multicriteria decision-making (MCDM) methods for location selection of EVCS.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Liu, Quan, Xu, and Jeffrey (2019) analyzed the relationship between optimal government subsidy rate and CSR level and believed that compared with nongovernmental subsidies, a certain range of government subsidy can promote the members of the supply chain to assume social responsibilities and improve the overall performance of the supply chain and social welfare. Deng and Tian (2020) believe that subsidies for the electric vehicle market are effective. Among this stream of studies, the subsidy factors in closed‐loop supply chains are taken into account, but few works specifically refer to DS.…”
Section: Literature Reviewmentioning
confidence: 99%